Early diagenetic pyrite cementation influences molecular composition of sedimentary organic matter in the Dongying Depression, China. (June 2020) - Xu, Huiyuan; Hou, Dujie; Löhr, Stefan C.; Liu, Quanyou; George, Simon C.
Highlights: Anaerobic bacterial reworking of organic matter yields changes in hydrocarbons. Pyrite concretions protect lipid hydrocarbons from further alteration during burial. Diagenesis can significantly influence the n -alkane carbon isotopic compositions. Pyrite concretions contain useful information on palaeoenvironments/source inputs. Diagenesis drives significant variation in composition of organics at mm scale. Abstract: Micro-variations of lipid hydrocarbons and biomarkers in well-laminated shales have not been extensively documented, especially within different rock textures, fabrics and mineralogies. Comparison of a pyrite cemented zone and its surrounding sediment may offer a new perspective on mineral control on preservation of hydrocarbons and organic carbon. A black well-laminated shale comprising two adjacent and contrasting calcareous (light) and pyrite (dark) laminae at the millimetre scale was selected from the Eocene Shahejie Formation, Dongying Depression, Bohai Bay Basin. It was horizontally sliced to separate a pyrite cemented concretion from the unaltered laminated shale, and investigated using geochemical techniques to assess the heterogeneity of elements, minerals, microfossils and hydrocarbons within the two slices. Micro-scale changes in source inputs were noted. For instance, the 4α-methylsteranes, dinosteranes and the triaromatic dinosteranes show varying distributions between the two slices, attributed to slight differences in dinoflagellate contributions. Similarly, variation in the amount of bacterial sulfate reduction is indicated by variations in the aryl isoprenoid ratio, relative amount of isorenieratane, long-chain n -alkane carbon isotopic composition and other molecular indicators including the relative amounts of dibenzothiophene, dibenzofuran, methyldibenzothiophene and methyltrimethyltridecylchromans. The primary control on these variations appears to be different euxinic water conditions, but diagenesis has also influenced the distributions. Differential anaerobic bacterial reworking of organic matter and pyrite concretion protection are responsible for organic geochemical variations on a millimetre-scale in the shale. The pyrite concretion has an altered record of its thermal history, but has a more accurate record of the organic geochemistry of microfossils and water column conditions. This study shows the potential for future investigations of closely-spaced vertical variation in organic geochemical parameters that may shed light on rapid temporal variation in organic matter input and depositional environment.